CYP3A1 metabolism-based neurotoxicity of strychnine in rat. (15th April 2022) - Jiang, Yuan; Qin, Lin; Lu, Anjing; Chen, Juan; Wang, Jianmei; Zhang, Qianru; Lu, Yanliu; Gong, Qihai; Gao, Jianmei; Ma, Hong; Tan, Daopeng; He, Yuqi
Abstract: Strychnine is one of the main bioactive and toxic constituents of Semen Strychni. In the present study, the neurotoxic effects of strychnine, and the role of individual differences in metabolism on susceptibility to neurotoxicity of strychnine were investigated. The acute toxicity was observed by a single dose of strychnine (2.92 mg/kg, i.g.) in rats, the epileptic stages of rats were scored according to Racine's scale. The neurotoxicity of strychnine was evaluated by the levels of ROS, MDA, SOD and GSH in hippocampus, striatum, and cortex tissues measurements and histopathological analysis. The concentrations of strychnine in the plasma, hippocampus, striatum, and cortex tissues were determined using high performance liquid chromatography tandem mass spectrometry (LC-MS/MS). The expressions of the cytochrome P450, which is the most critical protein family involved in drugs metabolism, were detected by proteomics. The mechanism of susceptibility to neurotoxicity of strychnine was elucidated by correlation analysis among above indicators. The results indicated that striatum and cortex were the main toxic targets of strychnine, and the CYP3A1 might be a susceptible biomarker to neurotoxicity of strychnine. These results provide valuable insights into the neurotoxic susceptibility of strychnine that will aid in the rational clinical use of strychnine (possibly including Semen Strychni).